ANALISIS PENEGAKAN HUKUM PERETASAN SITUS WEBSITE OLEH SINDIKAT JUDI ONLINE - Mansur, Habil Ma’ruf; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: This article aims to examine law enforcement regarding website hacking carried out by online gambling syndicates, which is increasingly common in relation to website hacking crimes. Hacking is included in cybercrime. In some hacking cases, the settings and legal consequences have not been explained in detail. Therefore, the formulation of the problem is how to enforce the law against hacking crimes committed by online gambling syndicates. The research method uses a normative legal research type and is descriptive. Normative dialysis secondary data. Drawing conclusions using deductive logic. The research results show that hacking of websites by online gambling syndicates is included in the category of cybercrime and violates the ITE Law, the Criminal Code and can be processed in the legal realm. There are several obstacles in the law enforcement process because the perpetrators use unclear identities (manipulative), use new methods to carry out their actions, and the devices or technology used are increasingly sophisticated. Keywords: Hacking, Online Gambling Syndicates, Law Enforcement, Websites.